Factors Affecting Patients’Attitude and Behavioral Intention of Using Hospital Online Services in Shanghai, China - Jutang Li,; Wei Dong ,; Qizhen Gu, (Journal of Roi Kaensarn Academi, 2024)
This study conducts a survey at three hospitals in Shanghai, China, to explore the factors influencing patients' attitudes and behavioral intentions toward using hospital online registration systems. A five-point Likert scale was used to develop the questionnaire, which was then validated by three experts through an IOC test. Prior to the formal survey, 50 samples were tested for internal consistency and reliability. A total of 500 valid questionnaires were distributed, with data analyzed using SPSS for descriptive statistics and AMOS for confirmatory factor analysis (CFA) and structural equation modeling (SEM). The CFA results confirmed the adequacy of the factor structure and the model’s fit. Based on theoretical frameworks, the study introduces attitude, perceived usefulness, and satisfaction as mediating variables to examine the relationships between independent variables (such as perceived usefulness, social influence, and promotion conditions) and the dependent variable (behavioral intention). The findings show that satisfaction, social influence, and promotion conditions significantly impact behavioral intention, while perceived usefulness and perceived ease of use significantly affect attitude. Additionally, attitude was found to have a direct impact on behavioral intention. The results highlight that satisfaction, social influence, promotion conditions, perceived usefulness, perceived ease of use, and attitude significantly influence patients' behavioral intention to use the online registration system. Specifically, satisfaction, social influence, and promotion conditions directly influence behavioral intention, while perceived usefulness and perceived ease of use indirectly affect behavioral intention through their impact on attitude. Attitude also has a direct influence on behavioral intention. These findings provide important insights for promoting and developing digital health services, particularly in enhancing patients' acceptance and usage of online registration systems. Hospitals can improve adoption rates by focusing on increasing patient satisfaction, optimizing system usability, and leveraging social influence. The study also offers practical recommendations for policymakers and technology developers to facilitate the widespread adoption of digital health services. Future research could extend these findings to other regions and further investigate additional factors such as privacy protection and security.